(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Core PC—19, recovered from the central Tyrrhenian Sea (Western Mediterranean) during cruise BAN 80, was investigated with micropaleontological and stable isotopic techniques. The time interval spans from Late Pleistocene to Holocene; the biostratigraphic framework was provided by calcareous nannofossils. Two biozones (Emiliania huxleyi and E. huxleyi Acme Zones) and two distinct biohorizons (the Gephyrocapsa caribbeanica/E. huxleyi abundance reversal and the beginning of E. huxleyi Acme) were recognized. Calcareous nannofossils confirmed to be excellent indicators of surface water mass temperatures: two warrn and five cold episodes and five low—salinity events were pointed out. Planktonic foraminifera were quantitatively analyzed: large fluctuations in abundance were pointed out and a climatic curve was constructed. Data regarding changes of deep water assemblages were provided by benthic foraminifera. Oxygen and carbon isotopic composition was measured on tests of Globigerina bulloides or Globigerinoides ruber; isotopic curves were correlated with the faunal climatic one and plotted against the biostratigraphic framework. Isotopic stages 3 and 5 and substages 5a and 5e could be identified whereas stage 1 was recognized only partially. Climatic zones W, X, Y and Z could be tentatively identified. The paleoceanographic changes evidenced by the present study are consistent with those known. for the eastern Mediterranean: thus Quaternary paleoclimatic and paleoceanographic signals had a large significance at least at regional scale.